Substance and structure in Columbia School linguistics. Issue 1 (2nd January 2016) - Davis, Joseph
ABSTRACT: In the debate over the proper roles in linguistics of substance and structure, the Columbia School has taken an explicit position: that both substance and structure are required for a successful analysis. In a particular linguistic problem, the relevant phonetic or semantic substance must be identified, and the structural, or value, relations within it must be specified, for an accounting of the distribution of forms in discourse. The rationale for this position was given by the founder of the school, William Diver, in1974, and the position has guided research since then. Ongoing research reported here on the Italian clitic si provides support for the appeal to both substance and structure.